Constructed Images of Iguazú National Park (Argentina) Related to Visitors’ Origins - A., Faggi; Hólzl, T.; Madanes, N.; Breuste, J.; Perelman, P. (European Scientific Journal, ESJ, 2017)
We analyzed the perceptions of tourists visiting the famous waterfalls in Iguazú National Park to define how they envisaged the park with their constructed images. Nine hundred and seventy six questionnaires were completed by personally interviewing visitors in February and April 2011. They were asked to describe the park by choosing between 17 fixed features (tranquility, grandiosity, water, harmony, beauty, horizon, sound of nature, colors, rainforest, extension, green, maintenance, animals, diversity, nature, peace and wilderness) and also an open option. The constructed images were classified in categories of Beauty, Sublime, Picturesque and Spiritual and explored with SPSS and multivariate analyses. Results showed that the appeal of the waterfalls is multidimensional, combining different elements of the Picturesque, Sublime, Beauty, and also Spiritual, categories in different proportions. We identified associations between visitors’ origins and the constructed images among groups of visitors from North America, Latin-America, Europe, Australia, South Africa and East Asia. We confirmed the widespread election of picturesque and sublime features as visions with which to describe the national park. Water, beauty and grandiosity were the main features mentioned. Peace, tranquility and horizon were found as possible explanations for the divergence in visions between the six groups studied, especially segregating East Asians and South Africans from the other groups. The observed similarities and differences in the constructed images of Iguazú National Park of visitors coming from different parts of the world could be explained by both evolutionary and cultural frameworks. Some recommendations for park management and city planning are given.